“Estudio comparativo de cuatro dosis de tetrahormonas en la producción del cultivo de tomate (lycopersicum esculentum mill) usando el híbrido wsx 2205 en el distrito de Lamas” - García García, Ricardo (2013)
The comparativa study of tetrahormonas cuatro dosis crop production in tomato (lycopersicon esculentum Mill) using the hybrid WSX2205 in the District of Lamas, hadas its overall objective: To determine the most appropriate dose of tetrahormonal bioestimulante (Biogyz) in crop yield tomato (Lycopersicon esculentum Mili) hybrid WSX 2205 F-1 in the district of Lamas and specific objectives: to evaluate and analyze the effect of four doses of tetrahormona (Biogyz) crop production in tomate (lycopersicon escutentum MHI) using 2205 WSX hybrid F-1, in the district of lamas and perform economic analysis of treatments. The present research work was carried out in the Horticultura! Fundo "The Pacific", owned by Jorge Luis Pelaez Rivera, in the district and province of Lamas. Conditions Horticultura! texture Fundo "The Pacif;c" is Sandy Loam, pH 5.57 - 6.0, 3.17 organic matter, available phosphorus 14.4 ppm. Tomato vegetative seed was used , hybrid WSX 2205 F- 1 and the treatments studied were: ( Dose Biogyz ) TO = Control , T1 = 100 cm3/ha (1.28 cc/3L water), T2 = 200 cm3/ha (2.56 cc/3L water) , T3 = 300 cm3/ha ( 3.84cc/3l water) and T4 = 400 cm3/ha (5.12 cc/3l water). The first application was made at flowering ( 20-40 % ) of open flowers and the second application was performed 2-3 weeks after the first appHcation. In both apptications, the tre-atments were repeated with the same dose raised. Furthermore, through the analysis of soil, vermicompost was applied in a general way and equal far all treatments. For the implementation of this research, Statistical Design of randomized complete block (RCBD) was used with five treatments and three replications. Data processing was performed using the program SPSS19 to a probability of 99% (P <0.01) and muttipte Ouncan test at P <0.05. The variables evaluated were: number of ftower clusters, number of flowers per cluster, number of fruits per harvest, fruit diameter, fruit length, fruit weight per harvest, Performance and Economic Analysis The main conclusions were that the treatment T4 (400 ce I ha) with the highest mean number of ftower clusters 24.6, 6.0 flowers per cluster, 10.12 cm fruit fength, weight 194.3 g fruit, fruit per plant 91.0 234,512.9 kg ha-1 and performance, being that treatment TO (control) received the lowest average on all variables evaluated, likewise, the treatment T 4 ( 400 ce I ha tetrahormona Biogyz) scored the best B I C with 15. 93. On the other hand, increasing tretrahormona applications defined a positive increasing and linear response defining a high correlation between the independent variable (dose tetrahormona) and the dependent variable.